Behavior of Pharmacists and Satisfaction of Patients in Coronavirus Disease-19 Pandemic - Iqbal, Dr. Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The aim of this study was to evaluate the behavior of the pharmacists and patients’ satisfaction in coronavirus disease-19 pandemic in Pakistan. Materials and Methods: A total of 314 participants participated in the study by cross-sectional study design and convenient sampling technique. Data were analyzed using Statistical Package for the Social Sciences. Results: Results revealed that significant number of respondents was not fully satisfied with behavior of the pharmacists. Around half of the respondents were agreed that pharmacists dispensed the same medication as prescribed by the prescribers. Around 38.9% of respondents noticed that pharmacists were not taking keen interest in resolving their health issues. Statistically, significant association (P < 0.05) was observed among patients’ overall satisfaction with pharmacists’ behavior and services, and precise dispensing of medications, medications counseling, interest in resolving patients’ health problems, and general attention given by the pharmacists toward patients. Conclusion: The study concluded that pharmacists should pay more attention to deal with their patients, especially during such pandemics when there is a more need of empathy and good behavior to increase patients’ satisfaction and decrease health-related problems.